Non-invasive care technologies: nurses' contributions to the demedicalization of health care in a high-risk maternity hospital - Juliana Amaral Prata; Lana Priscila Meneses Ares; Octávio Muniz da Costa Vargens; Carlos Sérgio Corrêia dos Reis; Adriana Lenho de Figueiredo Pereira; Jane Márcia Progianti (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: to discuss the use of non-invasive care technologies by nurse-midwives in a high-risk maternity hospital. Method: a descriptive and qualitative study with ten nurse-midwives who work at the obstetric center of a high-risk maternity at a university hospital in Rio de Janeiro City. Data collection took place in June and July 2017, through a semi-structured interview. The material was submitted to content analysis. Results: The participants use non-invasive care technologies from the perspective of health work technologies and demedicalization, setting up a care process centered on sensitive work and soft technologies. Thus, they shift the focus away from interventionist procedures and develop a care based on human relationships, integrality and female protagonism. Conclusion: with these technologies, nurse-midwives perform a new way of caring in high-risk maternity hospitals, contributing to the humanization of care and rearrangement of these fields. Implications for the practice: the use of these technologies drives the change of the care model by focusing on sensitive work and soft technologies instead of rough work and procedural hegemony.